A smart multiantenna gene theranostic system based on the programmed assembly of hypoxia-related siRNAs - Xue Gong (Nature Portfolio, 2021)
The therapeutic application of small interfering RNA (siRNA) is challenging due to its non-specific targeting and delivery issues. Here, the authors report an endogenous micro-RNA guided and hybridisation chain reaction-promoted siRNA delivery system encapsulated in tumour-derived extracellular vesicles, with cancer-specific activation, and achieve silencing of hypoxia-related genes.